The Discovery and Development of Natural-Based Biomaterials with Demonstrated Wound Healing Properties: A Reliable Approach in Clinical Trials - Nur Izzah Md Fadilah; Manira Maarof; Antonella Motta; Yasuhiko Tabata; Mh Busra Fauzi (Biomedicines, 2022)
Current research across the globe still focuses strongly on naturally derived biomaterials in various fields, particularly wound care. There is a need for more effective therapies that will address the physiological deficiencies underlying chronic wound treatment. The use of moist bioactive scaffolds has significantly increased healing rates compared to local and traditional treatments. However, failure to heal or prolonging the wound healing process results in increased financial and social stress imposed on health institutions, caregivers, patients, and their families. The urgent need to identify practical, safe, and cost-effective wound healing scaffolding from natural-based biomaterials that can be introduced into clinical practice is unequivocal. Naturally derived products have long been used in wound healing; however, clinical trial evaluations of these therapies are still in their infancy. Additionally, further well-designed clinical trials are necessary to confirm the efficacy and safety of natural-based biomaterials in treating wounds. Thus, the focus of this review is to describe the current insight, the latest discoveries in selected natural-based wound healing implant products, the possible action mechanisms, and an approach to clinical studies. We explore several tested products undergoing clinical trials as a novel approach to counteract the debilitating effects of impaired wound healing.